Protracted Clonal Trajectory of a JAK2 V617F-Positive Myeloproliferative Neoplasm Developing during Long-Term Remission from Acute Myeloid Leukemia - Stephen E. Langabeer; Karl Haslam; Maria Anne Smyth; John Quinn; Philip T. Murphy (Case Reports in Hematology)
Although transformation of the myeloproliferative neoplasms (MPNs) to acute myeloid leukemia (AML) is well documented, development of an MPN in patients previously treated for, and in remission from, AML is exceedingly rare. A case is described in which a patient was successfully treated for AML and in whom a JAK2 V617F-positive MPN was diagnosed after seven years in remission. Retrospective evaluation of the JAK2 V617F detected a low allele burden at AML diagnosis and following one course of induction chemotherapy. This putative chemoresistant clone subsequently expanded over the intervening seven years, resulting in a hematologically overt MPN. As AML relapse has not occurred, the MPN may have arose in a separate initiating cell from that of the AML. Alternatively, both malignancies possibly evolved from a common precursor defined by a predisposition mutation with divergent evolution into MPN through acquisition of the JAK2 V617F and AML through acquisition of different mutations. This case emphasizes the protracted time frame from acquisition of a disease-driving mutation to overt MPN and further underscores the clonal complexity in MPN evolution.